Pengembangan Bahan Ajar Pendidikan Agama Islam Berbasis Kecerdasan Emosional dan Kecerdasan Spiritual Kelas X di SMA IT Wahdah Islamiyah Pomalaa - Fatmawaty Fatmawaty; Muh. Askari Zakaria; Hartono Hartono (Journal on Education, 2023)
The teaching materials for Islamic Religious Education used at SMA IT Wahdah Islamiyah Pomalaa, especially for class X in the odd semester, are only more focused on developing aspects of intellectual intelligence, and this is very ironic when it is related to the contents of Law No. 20 of 2003 on the National Education System, which says that the purpose of national education is to foster the knowledge, skills, and morals of students. So in this context, it is not only the intellectuals that are developed but also the moral aspects of students, which are closely related to the values of emotional intelligence and spiritual intelligence. The purpose of this research is to develop Islamic Religious Education teaching materials based on emotional intelligence and spiritual intelligence by combining the theories of Daniel Goleman, Danar Zohar, and Ian Marshal, as well as the theory of Tazkiyah al-Nafs from Imam al-Ghazali, who has the values of validity, practicality, and effectiveness, to accommodate the needs of educational institutions and students. The research method used is development research with the ADDIE model, which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The results obtained from this study indicate that the development of teaching materials based on emotional intelligence and spiritual intelligence is something that is really needed as a complement to intellectual intelligence. And in the development of this teaching material, we obtained a validity value of 4.3 (very valid), a practicality value of 3.03 (practical), and an effectiveness value with the N-Gain test of 0.46 (moderate category).